Manganese removal using natural microflora - Mohd Kamarul Syahid, Salleh (2009)
The removal process of heavy metals from wastewater and industrial wastes has become a very environmental issue. The main scope of this study is to monitor the removal of manganese concentration in the biological treatment of simulated manganese wastewater using mixed culture from soil. The study is carried out in two phase consist of acclimatize phase and treatment phase. In the acclimatize phase, mixed culture from soils is inoculated in a 10 L reactor and the growth of the mixed culture is monitored. In the mean time, the mixed culture is fed with glucose solution and a trace amount of manganese solution. In the treatment phase, the mixed culture is used to treat simulated manganese wastewater. The experiments are carried in 15 days of period at 8 different loading rates which has been decided by the Design-Experts software. The degradation of manganese was monitored at three different water quality parameters which are the suspended solids, the chemical oxygen demand (COD) and the manganese concentration respectively. The experimental results show that, LR 3.0 mg/L.d shows the highest percentage of manganese removal at 87.50% with mean removal efficiencies of 77.70%. Also, LR 3.0 mg/L.d shows the highest percentage of COD removal at 83.77% with mean removal efficiencies of 73.45%. Based on Design-Expert analysis, it shows that, in order to achieve maximum of manganese concentration and COD removal, the loading rate need to be lowered. As the conclusion, the mixed culture in soils is capable of degrading manganese at which the effective loading rate for this study is 3.0 mg/L.d. -Author-